Synthesis and characterization of magnesium doped calcium phosphatefor bone implant application - Syed Abu Bakar, Sharifah Adzila; Kanasan, Nanthini; Hassan, Mohd Fahrul; Tajul Arifin, Ahmad Mubarak; Yunos, Muhamad Zaini; Abdol Rahman, Mohd Nasrull; Abdul Haq, Reazul Haq (Asian Research Publishing Network (ARPN), 2016)
Calcium phosphate (CaP) has been extensively studied for its excellent performance in promoting bone tissues ingrowth or osseointegration as in bone graft substitute and biomimetic coating of prosthetic implants. However poor mechanical properties of CaP has made its limited in a load bearing application and it has become an interests in research investigation for biomedical applications challenging. Here we employ an optimized mechanochemical method to synthesis calcium phosphate and Magnesium-doped Calcium Phosphate (Mg-CaP) in various weight percentages. The change of adsorption band in FTIR indicates that the Mg has been substituted into CaP. Doping by MgOH is found to effectively increase the densification and hardness of CaP when sintered at 1200 oC. Mg doping could be contributes to the improvement in artificial implant of calcium phosphate (CaP) for bone implant application in load bearing area.